Prediction of Loan Approval using Machine Learning - Kumar, Rajiv; Jain, Vinod; Sharma, Prem Sagar; Awasthi, Shashank; Jha, Gopal (International Journal of Advanced Science and Technology, 2019)
Loan approval is a very important process for banking organizations. The system approved or reject the loan applications. Recovery of loans is a major contributing parameter in the financial statements of a bank. It is very difficult to predict the possibility of payment of loan by the customer. In recent years many researchers worked on loan approval prediction systems. Machine Learning (ML)techniques are very useful in predicting outcomes for large amount of data. In this paper three machine learning algorithms, Logistic Regression(LR), Decision Tree (DT) and Random Forest (RF)are applied to predict the loan approval of customers. The experimental results conclude that the accuracy of Decision Tree machine learning algorithm is better as compared to Logistic Regression and Random Forest machine learning approaches.